1997
DOI: 10.1073/pnas.94.17.9165
|View full text |Cite
|
Sign up to set email alerts
|

CENP-E is an essential kinetochore motor in maturing oocytes and is masked during Mos-dependent, cell cycle arrest at metaphase II

Abstract: CENP-E, a kinesin-like protein that is known to associate with kinetochores during all phases of mitotic chromosome movement, is shown here to be a component of meiotic kinetochores as well. CENP-E is detected at kinetochores during metaphase I in both mice and frogs, and, as in mitosis, is relocalized to the midbody during telophase. CENP-E function is essential for meiosis I because injection of an antibody to CENP-E into mouse oocytes in prophase completely prevented progression of those oocytes past metaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…This suggests that one of the functions of active MAPK on kinetochores during mitosis is to regulate the interaction of CENP-E with microtubules and monitor mitotic progression. Inasmuch as CENP-E is essential for the spindle assembly checkpoint (Abrieu et al 2000), CENP-E is a possible target for CSF arrest, because CSFarrested spindles in both Xenopus and mouse eggs have been reported to have certain CENP-E epitopes masked compared with spindles in meiosis I or mitosis (Duesbery et al 1997). In addition, these epitopes are unmasked in oocytes from mos −/− mice, suggesting that CENP-E is phosphorylated downstream of Mos activity during meiosis II.…”
Section: Signaling the Spindle Checkpoint: The Importance Of The Kinementioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that one of the functions of active MAPK on kinetochores during mitosis is to regulate the interaction of CENP-E with microtubules and monitor mitotic progression. Inasmuch as CENP-E is essential for the spindle assembly checkpoint (Abrieu et al 2000), CENP-E is a possible target for CSF arrest, because CSFarrested spindles in both Xenopus and mouse eggs have been reported to have certain CENP-E epitopes masked compared with spindles in meiosis I or mitosis (Duesbery et al 1997). In addition, these epitopes are unmasked in oocytes from mos −/− mice, suggesting that CENP-E is phosphorylated downstream of Mos activity during meiosis II.…”
Section: Signaling the Spindle Checkpoint: The Importance Of The Kinementioning
confidence: 99%
“…In the maturing oocyte, these spindles are organized in the absence of centrioles, and ␥-tubulin-staining foci are not found at the spindle poles (McKim and Hawley 1995;Waters and Salmon 1995;Heald et al 1996;Matthies et al 1996). Rather, chromosomes themselves have been suggested to play a role in organizing microtubules and the meiotic spindle through regulation of microtubule-associated proteins and kinesin-like microtubule motors (Hatsumi and Endow 1992;Theurkauf and Hawley 1992;McKim and Hawley 1995;Waters and Salmon 1995;Matthies et al 1996;Duesbery et al 1997;Giunta et al 2002;Lefebvre et al 2002). It has been suggested that one of the targets of CSF activity during the establishment of CSF arrest is microtubule-associated proteins important for the establishment of the metaphase spindle (Duesbery et al 1997;Lefebvre et al 2002).…”
Section: Csf Arrest and Spindle Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the proteins responsible for the II metaphase arrest is the CENP-E, a kinetochore motor, which is probably masked during the arrest (Duesbery et al 1997). A comparison between starfish and Xenopus oocyte maturation is reported in Figure 3.…”
Section: Xenopusmentioning
confidence: 99%
“…109 For the latter role, Bub1 may function through controlling Shugoshin (see below) localization according to results obtained from mitosis. 61,62 CENP-E function is essential for meiosis I in pig, 110 mouse, rat and frog, 111,112 since it is a binding partner of BubR1. The localization of MAP kinase kinase (MEK) and MAP kinase is similar to some spindle checkpoint proteins [113][114][115][116][117][118] in oocytes.…”
Section: Spindle Checkpoint Proteins In Mammalian Meiosis Imentioning
confidence: 99%